Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms222212326
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptors in Myocardial and Cerebral Ischemia—Mechanisms of Action and Therapeutic Strategies

Abstract: Nearly 18 million people died from cardiovascular diseases in 2019, of these 85% were due to heart attack and stroke. The available therapies although efficacious, have narrow therapeutic window and long list of contraindications. Therefore, there is still an urgent need to find novel molecular targets that could protect the brain and heart against ischemia without evoking major side effects. Nuclear receptors are one of the promising targets for anti-ischemic drugs. Modulation of estrogen receptors (ERs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 278 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…The basic characteristics of AHR AHR is a ligand-controlled transcription factor (5), which is implicated in multiple physiological and pathological processes of many diseases, including inflammatory bowel disease (78), metabolic syndrome, and CNS diseases (79,80). Expression of AHR is widely detected in the CNS, such as in neurons, oligodendrocytes, monocytes/macrophages, astrocytes, microglia, and cerebral endothelial cells (81). AHR can regulate the expressions of target genes which relate to cell proliferation, metabolism and immune response (82).…”
Section: The Role Of Ahr In Ischemia Strokementioning
confidence: 99%
“…The basic characteristics of AHR AHR is a ligand-controlled transcription factor (5), which is implicated in multiple physiological and pathological processes of many diseases, including inflammatory bowel disease (78), metabolic syndrome, and CNS diseases (79,80). Expression of AHR is widely detected in the CNS, such as in neurons, oligodendrocytes, monocytes/macrophages, astrocytes, microglia, and cerebral endothelial cells (81). AHR can regulate the expressions of target genes which relate to cell proliferation, metabolism and immune response (82).…”
Section: The Role Of Ahr In Ischemia Strokementioning
confidence: 99%
“…By regulating renal organic transporters MATE-1 and OCT-2, PPAR deletion reduces cisplatin nephrotoxicity [29]. In mouse myeloid cells, knocking down PPAR γ in mouse myeloid cells led to cardiac hypertrophy and increased myocardial infarct size [30]. Studies in mice with macrophagespecific deletion of PPARγ have shown that PPARγ is required for the maturation of AAMacs [31].…”
Section: Ppars Deletion Studiesmentioning
confidence: 99%
“…After experimental ischemia, there is already evidence that SERMs imitate the effect of estradiol, minimizing hormone‐dependent concerns. Tamoxifen substantially decreased infarct size and protected neurons from ischemia in rats treated to permanent MCAO (pMCAO) 85 . Recently, a novel type of estrogen receptor G protein‐coupled estrogen receptor (GPER, formerly known as GPR30) broadly distributed throughout the brain might possibly play a crucial role in estrogen‐mediated neuroprotective benefits in pathologies like stroke 86 .…”
Section: Implications Of Different Xrs In Strokementioning
confidence: 99%
“…Tamoxifen substantially decreased infarct size and protected neurons from ischemia in rats treated to permanent MCAO (pMCAO). 85 Recently, a novel type of estrogen receptor G protein-coupled estrogen receptor (GPER, formerly known as GPR30) broadly distributed throughout the brain might possibly play a crucial role in estrogen-mediated neuroprotective benefits in pathologies like stroke. 86 This study reported that the GPER can be taken as a potential therapeutic target for stroke, mainly in males, as they cannot be exposed to estrogen therapy.…”
Section: Estrogen Receptors In Strokementioning
confidence: 99%